The Relationship Between Emotional Dysregulation and Aggressive Tendencies in Late Adolescent Who Are Sensitive to Crticism and Feel Unappreciated - Fani Oktaviani Agustin; Erik Saut H Hutahaean; Ferdy Muzzamil (Socrates: Journal of Education, Philosophy and Psychology, 2026)
This study aims to examine the relationship between emotional dysregulation and aggressive tendencies among late adolescents in Bekasi City. A quantitative method with a correlational approach was used. The subjects of this study were late adolescents residing in Bekasi City. Data were collected using the Emotional Dysregulation Scale and the Aggressive Tendencies Scale. The results of the study indicate that there is a significant positive relationship between emotional dysregulation and aggressive tendencies, with a correlation coefficient of 0.555 and a significance level of 0.001 (p < 0.05). This suggests that the higher an individual’s level of emotional dysregulation, the higher their aggressive tendencies. The strength of the relationship falls into the moderate category, indicating that other factors also influence aggressive tendencies. Additionally, the majority of respondents fall into the moderate category for both emotional dysregulation and aggressive tendencies. Based on the research findings, it is recommended that individuals improve their emotional regulation skills and manage their emotions more adaptively to reduce aggressive tendencies. Further research is recommended to expand the scope of the study and use direct measures of aggressive behavior.